Selected letters of Libanius : from the Age of Constantius and Julian - Libanios, 314-393 (Translated texts for historians ;, 2004)
Libanius of Antioch (AD 314–393) stands out as a fundamental source for the history of the Greek East in the fourth century AD. Drawn from the 1269 letters written between 355 and 365, the 183 letters presented here play an important role in making the age of Constantius II and Julian the Apostate the best-documented period of the ancient world.